PARENTAL COMPLIANCE WITH ROUTINE CHILDHOOD IMMUNIZATION AMONG CHILDREN 0-24 MONTHS - Istiana Syamsiati Savira; Ratih Sakti Prastiwi; Nanda Bachtiar (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Immunization is an essential strategy to protect children from vaccine-preventable diseases. In Indonesia, achieving complete immunization coverage remains a challenge at the primary health care level, including in Tegal Regency, where immunization coverage requires continuous evaluation to ensure all children receive timely vaccination. The success of immunization programs depends not only on the availability of health services but also on parental compliance in bringing children for immunization according to the recommended schedule. This study aimed to describe the level of parental compliance in bringing children aged 0–24 months for timely basic immunization in the working area of Suradadi Primary Health Center. A quantitative study with a descriptive survey design was conducted among parents of children aged 24–36 months. A total of 22 respondents were selected using quota sampling based on predefined inclusion criteria. Data were collected through observations of maternal and child health (MCH) books and children's immunization records and analyzed descriptively using frequency distributions and percentages. The findings showed that most respondents were of productive age, had completed secondary education, and were housewives. Overall, 20 respondents (90.9%) were compliant with the recommended immunization schedule, while 2 respondents (9.1%) were non-compliant. The high level of compliance indicates that most parents appropriately utilized immunization services according to the schedule. Strengthening health education, optimizing the role of community health volunteers, and implementing reminder systems are needed to maintain and improve parental compliance and ensure equitable immunization coverage among children.